Prenatal Diagnosis of Robin Sequence: Sensitivity, Specificity, and Clinical Relevance of an Index for Micrognathia. (August 2021) - Kruse, Teresa; Neuschulz, Julia; Wilhelm, Lucas; Ritgen, Jochen; Braumann, Bert
Objective: Micrognathia in connection with glossoptosis (called Robin sequence) may lead to life-threatening respiratory problems immediately after birth. An objective detection during prenatal routine ultrasound sonography is possible using an index that relates fetal lower jaw length to femur length or gestational age. The aim of this study was to test the method's sensitivity and specificity and to discuss its predictive power concerning neonatal respiratory insufficiency. Design: Patients with subjectively identified suspicious signs in the sagittal profile view were included in the study: Two-dimensional serial ultrasound scans of their fetal mandible were used to measure the lower jaw lengths and compare them to predicted values according to an index, derived from 313 healthy fetuses. Follow-up data provided additional information on the clinical appearance of the newborns. Results: The index showed a high sensitivity: 15 of the 16 cases with a micrognathia were correctly diagnosed (sensitivity of 93.75%). Follow-up data showed that newborns with similar index values differed in terms of their upper airway obstruction and treatment need. Conclusion: Fetal mandibular micrognathia can be objectively evaluated with the help of the index. The method allows an early detection of micrognathia, which helps to take the necessary steps for proper treatment of potential life-threatening respiratory impairment. Observations ranging outside the prediction interval could prompt the ultrasonographer to check for other associated malformations.